Impact of a Smartphone App Reminder on Adherence to Aspirin Prescribed as Antithrombotic Therapy. (November 2020) - Wittig-Wells, Deborah; Higgins, Melinda; Carter, Jessica; Holmes, Estella; Jacob, Ani; Samms-McPherson, Jacqueline; Sapp, Pam; Sims, Sandra; Titus, Bobina; Haupt, Jessica; Holstad, Marcia
Abstract : BACKGROUND: Many patients are discharged with aspirin (ASA) as an anticoagulant after joint replacement surgery. In studies in which ASA was prescribed, doses were frequently missed. Adherence to postoperative ASA regimen is critical to preventing thrombotic complications. This randomized controlled study evaluated the impact of an existing medication adherence smartphone application (app) on adherence to twice daily ASA 81 mg for 35 days after knee or hip arthroplasty. METHODOLOGY: Patients were randomized to either the app (intervention) group or the usual care (control) group. All patients received a baseline interview with a survey and demographics collected prior to randomization, a 36-day follow-up call for phone pill count, and a 6-week in-office interview with surveys and an in-person pill count. A convenience sample of 195 patients enrolled; 122 completed pill counts at both baseline and end of study. Ages ranged from 29 to 89 (mean: 60.4, SD: 10.1) years. The majority had a bachelor's degree or higher (59.3%), made more than $75, 000 (or were retired; 51.9%), were of White race (75.9%), and female (53.8%). There were no significant demographic differences between the groups. RESULTS: There were no significant group differences in final pill counts, adherence (reasons for missed pills), or ASA Medication self-efficacy scores. However, the intervention group scored significantly higher on the ASA Adherence measure (general ease in and ability to take ASA; p = .020). Higher ASA Adherence scores were associated with lower pill counts at the end of study (better adherence) in the intervention group. There was a high rate of attrition related to failure to bring the ASA to hospital or to the follow-up appointment. CONCLUSIONS: Although there were no significant differences in final pill counts between groups, the app group reported more ease in taking pills. With smartphone use virtually ubiquitous, this project provided an opportunity to educate patients and nurses about how technology can support medication adherence. It was also an excellent opportunity to involve clinical nurses in a funded research project.